Antimicrobial susceptibility patterns of bacillus anthracis isolates obtained from different origins - Elif ÇELİK; Aliye GÜLMEZ SAĞLAM; Fatih BÜYÜK; Salih OTLU; Mitat ŞAHİN; Özgür ÇELEBİ; Mustafa Reha COŞKUN; Seda GÖKDEMİR; Yaren ERSOY; Eray BÜYÜK; Bengisu ERŞAHİN (Kafkas Universitesi Veteriner Fakültesi Dergisi)
In this retrospective study, it was evaluated the antimicrobial susceptibility profiles of Bacillus anthracis isolates obtained from human, various samples (blood, spleen, lung, liver, meat) of dead animals (cattle, sheep, dog, horse) that died from anthrax and soil samples from the animal burial areas between 2012 and 2023 from Kars province of Türkiye. In this context, a total of 87 B. anthracis isolates obtained from 1 human, two horses, 51 cattle, 7 sheep, 1 dog, and 25 soil were investigated. The isolates were confirmed as B. anthracis using protective antigen (PA) and capsule (Cap) gen specific PCRs. The Kirby-Bauer disk diffusion method was used for deternination of antimicrobial susceptibility. Ten antimicrobials including penicillin, amoxicillin, trimethoprim-sulfometoxazole, erythromycin, meropenem, streptomycin, ofloxacin, ciprofloxacin, chloramphenicol, and clindamycin were tested. As a result of PCR, all isolates were confirmed as fully virulent field strains of B. anthracis. All isolates were found as susceptible to penicillin, amoxicillin, ofloxacin and ciprofloxacin. Since the last studies in the region, a change in the antimicrobial profile of B. anthracis strains was observed only for trimethoprim-sulfomethoxazole among the antimicrobials tested, a transition from susceptibility to resistance. In conclusion, penicillin and amoxicillin, are still the antibiotic of first choice for the prophylaxis and treatment of anthrax. Ofloxacin and ciprofloxacin are also effective enough to be prescribed for treatment.